New fast-relaxed liquid crystal materials for optical communication networks - Garbovskiy, Yu.; Sadovenko, A.; Koval'chuk, A.; Klimusheva, G.; Bugaychuk, S. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
Recording the dynamic holograms with microsecond relaxation times under action of laser pulses was obtained in composites based on the novel class of liquid crystals (LC), namely in ionic metal-alkanoates. Holographic parameters of the recording and relaxation characteristics were studied for doped lyotropic ionic LC and sandwich-like cells with photo-sensitive impurities for purposes of real-time dynamic holography applications. The thin cells demonstrate high-velocity dynamic grating recording under laser pulses both of nanosecond and picosecond durations at the visible wavelengths. The cells exhibit a fast temperature relaxation time (with the time constant 30 μs for the store heat density more than 50 kJ/s). Ionic lyotropic smectic LCs possess a high intrinsic anisotropic conductivity as compared with other LCs – dielectrics. To explain the relaxation mechanisms in ionic smectic LC matrix, the temperature dependences of the electro-conductivity have been investigated. The charge currier mobility and activation energy in cells were estimated. The mechanism of high-velocity resonance nonlinearity due to the saturation of excited states in photosensitive centers and mechanisms of the grating erasure connected with charge transport in the ionic LC matrix were discussed.